Myopalladin promotes muscle growth through modulation of the serum response factor pathway. Issue 1 (24th October 2019) - Filomena, Maria Carmela; Yamamoto, Daniel L.; Caremani, Marco; Kadarla, Vinay K.; Mastrototaro, Giuseppina; Serio, Simone; Vydyanath, Anupama; Mutarelli, Margherita; Garofalo, Arcamaria; Pertici, Irene; Knöll, Ralph; Nigro, Vincenzo; et al.
Abstract: Background: Myopalladin (MYPN) is a striated muscle‐specific, immunoglobulin‐containing protein located in the Z‐line and I‐band of the sarcomere as well as the nucleus. Heterozygous MYPN gene mutations are associated with hypertrophic, dilated, and restrictive cardiomyopathy, and homozygous loss‐of‐function truncating mutations have recently been identified in patients with cap myopathy, nemaline myopathy, and congenital myopathy with hanging big toe. Methods: Constitutive MYPN knockout (MKO) mice were generated, and the role of MYPN in skeletal muscle was studied through molecular, cellular, biochemical, structural, biomechanical, and physiological studies in vivo and in vitro . Results: MKO mice were 13% smaller compared with wild‐type controls and exhibited a 48% reduction in myofibre cross‐sectional area (CSA) and significantly increased fibre number. Similarly, reduced myotube width was observed in MKO primary myoblast cultures. Biomechanical studies showed reduced isometric force and power output in MKO mice as a result of the reduced CSA, whereas the force developed by each myosin molecular motor was unaffected. While the performance by treadmill running was similar in MKO and wild‐type mice, MKO mice showed progressively decreased exercise capability, Z‐line damage, and signs of muscle regeneration following consecutive days of downhill running. Additionally, MKO muscle exhibited progressive Z‐line widening starting from 8 months of age. RNA‐sequencing analysis revealed down‐regulation of serum response factor (SRF)‐target genes in muscles from postnatal MKO mice, important for muscle growth and differentiation. The SRF pathway is regulated by actin dynamics as binding of globular actin to the SRF‐cofactor myocardin‐related transcription factor A (MRTF‐A) prevents its translocation to the nucleus where it binds and activates SRF. MYPN was found to bind and bundle filamentous actin as well as interact with MRTF‐A. In particular, while MYPN reduced actin polymerization, it strongly inhibited actin depolymerization and consequently increased MRTF‐A‐mediated activation of SRF signalling in myogenic cells. Reduced myotube width in MKO primary myoblast cultures was rescued by transduction with constitutive active SRF, demonstrating that MYPN promotes skeletal muscle growth through activation of the SRF pathway. Conclusions: Myopalladin plays a critical role in the control of skeletal muscle growth through its effect on actin dynamics and consequently the SRF pathway. In addition, MYPN is important for the maintenance of Z‐line integrity during exercise and aging. These results suggest that muscle weakness in patients with biallelic MYPN mutations may be associated with reduced myofibre CSA and SRF signalling and that the disease phenotype may be aggravated by exercise.